A walk in the park: a study of African American women and an opportunity for physical activity - Garrott, Lauren (Kansas State University, 2014)
In the United States, minorities are less physically active and in turn at higher risk for heart disease, diabetes and obesity. The purpose of my study is to examine the factors that influence physical activity in neighborhood parks and to answer: What aspects of park design and programming discourage physical activity participation in African American women? My goal is to identify barriers to physical activity and make recommendations for improving design and programming of a neighborhood park. The results of my research are relevant to the planning profession because planners can use public policy to combat inequality in the built environment. Many studies have related recreation access to socioeconomic status, race, ethnicity, age, and gender. While African American women are not the only disadvantaged population when it comes to access to recreation, they do have a higher risk for obesity. In trying to answer why African American women have higher rates of obesity, some studies have found that while willingness to participate in physical activity does not differ in white and black women, duration of physical activity does. My research employs a mixed methods approach to understand the barriers to physical activity experienced by African American women, in context of a neighborhood park. This study uses a physical assessment of James Mulligan Park and the surrounding neighborhood within Alexandria, Virginia. Following the physical assessment I piloted a survey to gather information on the barriers to physical activity. The pilot guided a final survey of seventeen participating African American women in the neighborhood. I hypothesized that the perception of park safety will have an effect on the rate of physical activity in African American women. This hypothesis points to a general barrier for all women. Based on literature review, I also expected to find barriers unique to African American women. The study concluded that African American women in this neighborhood share some barriers with all women and they also expressed some barriers unique to African American women. I found that personal barriers like “exercise tires me” was the most common, rather than perceptions of safety. In addition, I found culturally specific barriers, such as “exercising is not my cultural activity” and “I avoid exercise to protect my hairstyle.” Based on my analysis of the setting and surveys I make several recommendations for the park and neighborhood.
Keywords: Parks and recreation; Park planning; African American women; Physical activity; African American Studies (0296); Public Health (0573); Recreation and Tourism (0814); Urban Planning (0999)